Catia customization for Design and Modeling of Two stage spur Gearbox - Patwardhan, Mayuresh V.; Nimbalkar, Uddhavrao (International Journal of Advanced Science Computing and Engineering, 2021)
In this paper, we describe how the customization of design task, in solid modeling with CATIA V5 for two stage spur gearbox can be approached, by means of macros (piece of code) and with GUI form. The user has to supply some basic requirements of the gearbox and rest of the different parameters for design of gearbox is calculated by formulas. And then with the help of these parameters, part model of gearbox is created.